2014
DOI: 10.1111/ene.12468
|View full text |Cite
|
Sign up to set email alerts
|

Association between migraine and irritable bowel syndrome: a population‐based retrospective cohort study

Abstract: The current population-based study demonstrated that migraine is associated with an increased risk of IBS after adjusting for comorbidities, particularly in the young population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 41 publications
4
51
0
1
Order By: Relevance
“…A recent population-based retrospective cohort study in Taiwan found that the incidence of IBS was 1.95-fold higher in the migraine cohort than non-migraineurs. This was particularly evident in the cohort of migraineurs younger than 30 years old, who exhibited a 3.36-fold increased risk of IBS [69]. It is theorized that the underlying pathophysiology of IBS and migraine is a genetically established hypersensitive or hyperexcitable brain.…”
Section: Migraine and Gi Disordersmentioning
confidence: 98%
“…A recent population-based retrospective cohort study in Taiwan found that the incidence of IBS was 1.95-fold higher in the migraine cohort than non-migraineurs. This was particularly evident in the cohort of migraineurs younger than 30 years old, who exhibited a 3.36-fold increased risk of IBS [69]. It is theorized that the underlying pathophysiology of IBS and migraine is a genetically established hypersensitive or hyperexcitable brain.…”
Section: Migraine and Gi Disordersmentioning
confidence: 98%
“…Similar adjustments increase the incidence figures from 68 to 70 per 10 000 for asthma23 and from 30.1 to 35.4 per 10 000 person-years for migraine 24. The corresponding figures for the 12 general population samples that were comparison cohorts for a specific general medical disorder was 43.8 (range 3-86.7) (Table 2).…”
mentioning
confidence: 90%
“…27,33,34 Other functional gastrointestinal disorders, such as dyspepsia and GERD, together with pain and sleep disorders have been shown to be very closely associated with IBS and might share a common aetiological pathway. 24,29,34 These are diverse and might be directly or indirectly associated with the aetiology of IBS. 24,29,34 These are diverse and might be directly or indirectly associated with the aetiology of IBS.…”
Section: Breadth and Strength Of Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…But the great majority of time is spent managing patients with primary headache such as Migraine. Headaches can be primary due to overactivity of pain-sensitive areas like nerves, blood vessels and muscles of head and neck or due to changes in chemical activity of brain in cases of Migraines and Secondary due to conditions that stimulate these pain-sensitive areas as in GERD (3,17,42) .…”
Section: Discussion and Conclusion:-mentioning
confidence: 99%